Pricing Paris Hotel Rooms: A Hedonic Pricing Approach - Meahan, Sam A. (Université d'Ottawa | University of Ottawa, 2016)
This paper uses a hedonic pricing model to estimate the implicit returns of select hotel characteristics that contribute to overnight room rates of Paris hotels. The dataset used in this paper consists of pricing information on 410 hotels and the associated general, reputational, geographical, and locational characteristics. I find that the star rating, Palace hotel rating, and Trip Advisor rating play key roles in determining standard and premium room rates. Additionally, I find that the inclusion of Wi-Fi in the room rate, the number of rooms of in the hotel, and hotel proximity to the Eiffel Tower to be added determinants in the price of premium rooms only. A price-sensitivity analysis, using prices collected on three separate dates, shows that hotel prices do not tend to fluctuate significantly between the dates of price collection.